Bovine Dialyzable Leukocyte Extract IMMUNEPOTENT CRP: Evaluation of Biological Activity of the Modified Product - Franco Molina, Moisés Armides; Santana Krimskaya, Silvia Elena; Zárate Triviño, Diana Ginette; Zapata Benavides, Pablo; Hernández Martínez, Sara Paola; Cervantes Wong, Fernanda; Rodríguez Padilla, María Cristina (2021)
Dialyzable leukocyte extracts are clinically used under different commercial names (IMMUNEPOTENT CRP®, IMMODIN®, Transferon®) to modulate the immune response altered by pathological conditions such as cancer, inflammation, and viral infections. The purpose of this study is to improve the production process of bovine dialyzable leukocyte extract without decreasing its biological activities (antioxidant, anti-inflammatory, and antitumoral). Our product modification consists of adding a dry heating step in the production process. In this study, we evaluated and compared the chemical composition (bromatological analysis), physical structure (infrared spectroscopy, X-ray diffraction, SEM, and zeta potential) and biological function of the dialyzable leukocyte extracts obtained from fresh and dry bovine spleens. Our results showed that the use of a drying step in the production process of the bovine dialyzable leukocyte extract (bDLE) did not affect its antioxidant and anti-inflammatory effects and it improved its antitumor properties. We suggest that this process modification could be applied to other biological products, such as dialyzable leukocyte extracts derived from other sources, in order to improve its functionality and formulation.